Troponin destabilization impairs sarcomere-cytoskeleton interactions in iPSC-derived cardiomyocytes from dilated cardiomyopathy patients - Dai, Yuanyuan (NATURE PUBLISHING GROUP, 2023)
10.1038/s41598-019-56597-3